It is harder for me: A thematic analysis of lived experience of self-care, and its relationship with self-injurious behaviors in psychiatric patients - Jonas Bjärehed; Hanna Grenner; Sara Pavlovic; Magnus Nilsson (Qualitative Research in Medicine & Healthcare)
Self-injury is associated with significant psychological distress and functional impairments, including difficulties with self-care. However, little is known about how individuals engaging in self-injury perceive and manage self-care in their daily lives. This study aimed to explore the lived experiences of self-care among individuals receiving psychiatric treatment for self-injury and to identify factors that support or hinder self-care capacity. Twelve participants were recruited from a psychiatric outpatient clinic and semi-structured interviews were conducted focusing on participants’ perceptions of self-care, its relationship with self-injury, and factors influencing self-care. Reflexive thematic analysis was conducted to identify patterns and themes. The analysis revealed four themes: i) Why should I choose self-care?, highlighting motivational challenges rooted in low selfworth and the need for meaning; ii) Self-care is a difficult choice for me, reflecting how emotional variability, uncertainty about selfcare, and dichotomous thinking hinder decision-making; iii) Selfcare is beyond my control, emphasizing struggles with planning, routines, and the interplay of emotional states and self-care behaviors; and iv) Support can both help and hinder self-care, illustrating the critical yet complex role of external support. Findings highlight the multifaceted challenges individuals face in managing self-care and its intersection with self-injury. Clinical implications include the need for tailored, person-centered interventions that address barriers to self-care. Recognizing the dual role of self-injury—as both a barrier to and a risky form of self-care—may enhance treatment approaches for this population.